Kecerdasan budaya dan penyesuaian diri dalam konteks sosial budaya pada mahasiswa Indonesia yang kuliah di luar negeri - Ghaniyy, Anshari Al; Akmal, Sari Zakiah (Konsorsium Psikologi Ilmiah Nusantara, 2018)
This study aims to investigate the relationship between the sociocultural adjustment and cultural intelligence in Indonesian students who study abroad. Sociocultural adjustment is the ability and competence to adapt in a new environment by facing everyday life difficulties in different cultural contexts. Cultural intelligence is an individual's ability to learn, manage, and interact in order to work effectively with culturally different societies. Cultural intelligence has two dimensions: internalised cultural knowledge intelligence (ICK) and effective cultural flexibility (ECF). Participants in this study were 105 Indonesian students who studied abroad at the time they participate. The data was processed with partial correlation by controlling for sex and the use of English. The results showed that ICK has a significant relation to sociocultural adjustment, while ECF is not significantly related to sociocultural adjustment. The findings highlight the importance of students to deepen the cultural and all aspects of the destination country in order to adapt well.